Lyhytkirurginen potilas terveydenhuollon asiakkaana - Leino-Kilpi, Helena; Suominen, Tarja; Sosiaali- ja terveysalan tutkimus- ja kehittämiskeskus (Raportteja / Sosiaali- ja terveysalan tutkimus- ja kehittämiskeskus, ISSN 1236-0740, 1997)
Abstract: The patient undergoing short-stay and day care surgery as a client within health care service.
Keywords: Ambulatory Surgical Procedures; Anesthesia; Cataract Extraction; Health Knowledge, Attitudes, Practice; Home Nursing; Organization and Administration; Outpatients; Patient Education as Topic; anestesiologia; lyhytkirurgia; neuvonta; omaiset; potilaat; potilasneuvonta; silmätaudit; anestesiologi; dagkirurgi; rådgivning; anhöriga; patienter; patientinformation; ögonsjukdomar